Letters to and from Ludwig Tieck and His Circle Unpublished Letters from the Period of German Romanticism Including the Unpublished Correspondence of Sophie and Ludwig Tieck - Matenko, Percy; Zeydel, Edwin H.; Masche, Bertha M. (UNC Studies in the Germanic Languages and Literatures, 1967)
This monumental collection of 165 letters was acquired or reproduced in Europe before World War II. Fully edited, the letters between Tieck and his associates as well as between Ludwig and Sophie Tieck are an indispensable source of information on the author himself and the intellectual milieu of German Romanticism.